Old wine in new bottles: a county-level case study of anti-corruption reform in the People’s Republic of China - Chan, Hon S. (Crime, law and social change, 2008)
This paper examines the role of the target-based responsibility system for building upright Party style and clean government in combating corruption in local China. It argues that the effectiveness of the target-based responsibility system in corruption control is compromised by a number of implementation hurdles in practice. Based on a close examination of one county, Shaanxi Province in the northwest China, this study shows that low measurability of the targets, the conflict between anti-corruption work and other evaluation targets, and the impact of patronage politics account for the implementation failure of the target-based responsibility system. The fundamental problem lies in that under China’s unified cadre personnel management system, political will can interfere with the handling of corruption on a case-by-case basis, no matter what kind of anti-corruption mechanism is employed. Under this context, the adoption of the target-based responsibility system in fighting corruption results in nothing more than "pouring old wine into new bottles."